2005
DOI: 10.1007/3-540-26932-0_47
|View full text |Cite
|
Sign up to set email alerts
|

Results of the International Comparison of Absolute Gravimeters in Walferdange (Luxembourg) of November 2003

Abstract: The results of an international comparison of absolute gravimeters held in Walferdange Luxembourg in November 2003 are presented. The absolute meters agreed with one another with a standard deviation of less than 2 µGal (1 Gal = 1 cm/s2) (if we exclude one prototype instrument from the analysis). For the first time, the ability of the operators was put to the test. The comparison indicates that the errors due to the operator are less than 1 µGal, i.e. within the observational errors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…However, using different FG5 gravimeters can lead to gravity values with an rms error of up to 2 μGal (Robertsson et al 2001). This was confirmed by comparing 13 absolute gravimeters (including 11 FG5) in 2003 (Francis et al 2005): a standard deviation of 1.9 μGal was obtained. Consequently, Sato et al (2006) suggested to add 2 μGal in quadrature to all the formal errors and fit the data with the new error as a weight.…”
Section: Ground Gravity Measurementsmentioning
confidence: 64%
“…However, using different FG5 gravimeters can lead to gravity values with an rms error of up to 2 μGal (Robertsson et al 2001). This was confirmed by comparing 13 absolute gravimeters (including 11 FG5) in 2003 (Francis et al 2005): a standard deviation of 1.9 μGal was obtained. Consequently, Sato et al (2006) suggested to add 2 μGal in quadrature to all the formal errors and fit the data with the new error as a weight.…”
Section: Ground Gravity Measurementsmentioning
confidence: 64%
“…The target has often been the postglacial rebound (PGR), i.e., the viscoelastic response of the Earth to past changes in ice mass (glacial isostatic adjustment GIA), or the elastic response of the Earth to present-day deglaciation. The accuracy of modern absolute gravimeters is about m 0 = 2 Gal (one-sigma) (Niebauer et al, 1995;Francis et al, 2005). Assuming independent annual measurements, a trend in gravity can be determined in N years with the precision (12/(N(N − 1)(N + 1))) 1/2 m 0 or in 10 yr to 0.22 Gal/yr.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Intercomparison campaigns have shown systematic errors (offsets) between the different absolute gravimeters that are larger than the declared uncertainties [Vitushkin et al, 2002[Vitushkin et al, , 2010Francis et al, 2005Francis et al, , 2010. Although the offsets can be determined by comparing the instruments, this is always within uncertainties and not always logistically feasible.…”
Section: The Absolute Gravimetermentioning
confidence: 99%
“…Other malfunctioning components may also bias the AG [Wziontek et al, 2008]; this is why, before and after each campaign, the instrument measured at the Membach reference station, where it was compared with the continuously measuring superconducting gravimeter [Van Camp et al, 2005; Van Camp and Francis, 2006]. Finally, the FG5#202 was regularly compared to other AG meters [Robertsson et al, 2001;Vitushkin et al, 2002Vitushkin et al, , 2010Van Camp et al, 2003;Francis et al, 2005Francis et al, , 2010Baumann et al, 2010]. The FG5#202 also benefited from maintenances by the manufacturer in 1998, 2000, 2003, 2005, 2007 and 2010, where it was also compared to other FG5s.…”
Section: The Absolute Gravimetermentioning
confidence: 99%